The Effects of Meteorin-Like Protein on Diabetic Neuropathy: In Vivo and In Vitro Model Studies - Yuksel, Furkan; Taslidere, Asli; Ozcan, Mete; Tekin, Cigdem; Tekin, Suat (Wiley, 2025)
Diabetes is a disease characterized by insulin metabolism, and diabetic neuropathy (DN) develops as a result of prolonged hyperglycemia. Meteorin-like protein (Metrnl), which has been found to regulate insulin resistance in conducted studies, is thought to be therapeutic for type-2 diabetes. This study was conducted to investigate the efficacy of Metrnl on In Vivo and In Vitro diabetic neuropathy model. In study, 40 normoglycemic male Balb-C mice were divided into 4 groups (n = 10). Except for control, all groups received a single intraperitoneal (ip) injection of streptozotocin (STZ). After 72 h, blood glucose level was measured and animals above 250 mg/dL were considered diabetic. 14-day experiments were initiated 21 days after the onset of diabetes. Every day for 14 days, 0.9% isotonic sodium chloride was administered to DN group, and 2-4 mu g/kg/day ip Metrnl was administered to treatment groups, and nociceptive behavior tests were performed simultaneously. End of experiment, animals were decapitated, and pancreatic tissues were collected. Dorsal root ganglion (DRG) isolated from Wistar Albino rats aged 1-2 days were exposed to high glucose for 24 , and the effect of Metrnl on cell viability and cellular pathway it utilizes were determined. It was observed that Metrnl injection increased the pain threshold (p < 0.05), improved oxidative stress parameters (p < 0.05), and restored histopathological damage of the pancreas (p < 0.05) compared to the DN group. Furthermore, Metrnl was detected to increase cell viability by utilizing mitogen-activated protein kinase pathway in DRG (p < 0.05). These findings suggest that Metrnl has neuroprotective and analgesic efficacy and ameliorates oxidative damage and histopathologic status of pancreas.
Keywords: diabetes; DRG; metrnl; neuropathy; pain